Effects of Fish Oil Supplementation on Cardiometabolic Risk Factors in Overweight or Obese Children and Adolescents: A Meta-Analysis of Randomized Controlled Trials - Wu, Shaojing; Zhu, Chunhong; Wang, Zhen; Wang, Shumei; Yuan, Pengfei; Song, Tao; Hou, Xiaoli; Lei, Zhixian (Frontiers in Pediatrics, 2021)
Background: Influences of fish oil supplementation on body weight and other cardiometabolic factors in overweight or obese children and adolescents remain not fully understood. We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the role of fish oil for these children. Methods: Relevant studies were obtained by search of PubMed, Embase, and Cochrane’s Library databases. A random-effect model, which incorporates the potential heterogeneity of the included studies, was used to pool the results. Results: Twelve RCTs including 1,028 overweight or obese children and adolescents were included. Compared to control, fish oil supplementation significantly reduced body mass index (BMI, mean difference [MD]: -0.96 kg/m2, 95% confidence interval [CI]: -1.69 to -0.23, P=0.01), but did not significantly reduce body weight or waist circumference (P=0.68 and 0.76). Moreover, fish oil supplementation significantly reduced serum triglyceride (MD: -0.24 mmol/L, 95% CI: -0.40 to -0.08, P=0.004), but did not significantly affect serum total cholesterol, high-density or low-density lipoprotein cholesterol (P=0.83, 0.42, and 0.31, respectively). Additionally, fish oil supplementation significantly lowered systolic blood pressure (SBP, MD: -2.46 mmHg, 95% CI: -4.93 to -0.01, P=0.04), but did not significantly change diastolic blood pressure (P=0.22). Supplementation with fish oil did not significantly affect fasting plasma glucose (P=0.33). Conclusions: In overweight or obese children and adolescents, supplementation with fish oil could reduce BMI, decrease serum triglyceride, and lower SBP, while serum cholesterol and fasting glucose may not be significantly affected.